ANDROID-BASED BOAT RENTAL INFORMATION SYSTEM ON PANGANDARAN BEACH - Ima Maelani (LKP Tematik Aperta Nusantara, 2026)
Pangandaran Beach there is Lots very object interesting tours​ For visited by tourists . Tourists can enjoy beautiful sun rising on the East Coast and the sun sunset on the West Coast. In addition , tourists can also rent boat For middle sea and also around Good from the West Coast to the East or on the contrary . In rental boat moment This Still done manually , such as must come to moreover formerly to place rental boat . Meanwhile , now This everything want to all-round practical and not complicated when do rental boat the . So, for simplify the rental process boat that is with use android application that I made about rental boat at Pangandaran Beach . Through application This tenant can do booking online without​ need come to place rentals and more easy in determine desired location​ targeted as well as can pay it inside application the . If the research This succeed will produce A capable system​ help give convenience for second split parties , so that can expected later will simplify and speed up the service process , data storage and presentation return the data .